Correlation analyses of factors that affect the carrying capacity of the old strip foundation in the new piles reinforced one - Maievska, I. V.; Popov, V. O.; Blashchuk, N. V.; Chornoskutova, K. O. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The comprehensive analysis of the factors that affect the carrying capacity of pile-foundation grillage-tape for shallow foundation reinforced with piles is completed in the paper .According to the results of correlation analysis with elements of mathematical modeling the functional dependence of the bearing capacity of the existing strip foundation is obtained.